Cryopreservation of Zea mays L. embryonic axes - Fowler, Candace (My University, 2011)
The successful cryopreservation of a South African maize cultivar (Hybrid 6363) was not possible due to the large size of the intact caryopses. To overcome the problem the embryonic axes were isolated. Isolation of the axes from dry caryopses proved challenging and resulted in the damage of 50% of all axes isolated. To ensure the successful removal of the intact axes from the caryopses, imbibition over a period of 30 minutes to 6.5 hours was employed to soften the testa and the pericarp. The effects of imbibition and subsequent cryostorage on the sample water content, vigour and viability were assessed. The water contents of excised embryos increased considerably within the first 30 minutes of imbibition without any visible differences in viability for both the control and cryostored samples. Concomitantly, so were the results for the rest of the imbibition times tested. However, a comparison of the germination indexes indicated that vigour was impeded by cryostorage. In addition to reduced vigour of cryostored material, at the higher imbibition times, morphological aberrations were observed, for example, the lack of root formation. An ultrastructural investigation of the root meristems pre- and post-cryostorage provided information of the changes associated with imbibition as well as the subsequent effects of freezing and thawing. Successful cryostorage seemed to be associated with the lack of obvious metabolic activity at the ultrastructural level (retained desiccation tolerance). The possibility of the leached solutes, out of the caryopses, performing a cryoprotective rôle was considered as a further explanation of the observed post-cryostorage successes. The results confirmed that the combined concentrations of proline, γ-amino butyric acid, glycine, glutamic acid and glucose (known cryoprotectants) were sufficiently high and therefore hypothesized to behave as natural cryoprotectants, but only effectively prior to the acquisition of tissue desiccation sensitivity. Hybrid 6363 had aged in storage prior to and after its purchase, introducing cellular changes at the physiological and biochemical levels prior to any subsequent effects of imbibition and cryostorage. The onset of imbibition itself resulted in many physiological and structural changes and, subsequent cryostorage of tissue at higher water contents proved deleterious to the resulting plantlets. All of these effects were exacerbated in aged seed. It was therefore proposed that aged seed subjected to imbibition and subsequent cryostorage would sustain elevated damage and hence should not be considered for germplasm preservation purposes. Comparative studies were done between freshly harvested seed Hybrid 6321 and Hybrid 6363 (fresh Hybrid 6363 was unavailable). Marked differences were noted ultrastructurally and biochemically, but the lack of root formation was still observed in tissue hydrated for longer periods in Hybrid 6321. The eventuality that damage occurred at the ultrastructural level was investigated and it was found that the changes in cytoskeletal activity within Hybrid 6321, due to imbibition, were extensive within the first 6.5 hours. Cryostorage at specific hydration levels resulted in additional damage, however, the extent of this damage was dependent on the level of cytoskeletal organisation and is suggested to be associated with the tissue having lost or retained desiccation tolerance.